The Role of Pathogens in Bumblebee Decline: A Review - Huanhuan Chen; Nawaz Haider Bashir; Qiang Li; Chao Liu; Muhammad Naeem; Haohan Wang; Wenrong Gao; Richard T. Corlett; Cong Liu; Mayra C. Vidal (Pathogens)
Bumblebees, the most important wild pollinators in both agricultural and natural ecosystems, are declining worldwide. The global decline of bumblebees may threaten biodiversity, pollination services, and, ultimately, agricultural productivity. Several factors, including pesticide usage, climate change, habitat loss, and species invasion, have been documented in the decline of bumblebee species, but recent studies have revealed the dominating role of pathogens and parasites over any of these causes. Unfortunately, there is a lack of a full understanding of the role of pathogens and parasites in the decline of bumblebee species. The current study provides a comprehensive review of how pathogens and parasites contribute to the decline of bumblebee species. The study also explores the prevalence of each pathogen and parasite within bumblebee populations. Furthermore, we address the synergistic effects of pathogens and other stressors, such as pesticides, climatic effects, and habitat loss, on bumblebee populations. To summarize, we propose possible conservation and management strategies to preserve the critical role of bumblebees in pollination services and thus to support ecosystem and agricultural health.